Unsur-unsur Pendidikan dalam Hadis Muslim - Aulia Azizatul Hidayah; Hairul Hudaya (La-Tahzan: Jurnal Pendidikan Islam, 2026)
This study examines the educational elements found in Muslim Hadith, one of the most authoritative sources of Islamic teachings that contains essential pedagogical values and practices of the Prophet Muhammad The core problem discussed is how the traditions in Muslim Hadith illustrate the aims of education, the characteristics of educators and students, the structure of learning materials, and the instructional methods applied by the Prophet. This research employs a qualitative approach using a literature study method through textual analysis of hadiths and conceptual interpretation of scholarly works related to Islamic education. The findings reveal that Muslim Hadith presents educational goals emphasizing sound creed, the balance between knowledge and ethics, the cultivation of moderate character, and social responsibility through the transmission of good deeds (sunnah hasanah). Educators are depicted as knowledgeable, trustworthy, and exemplary figures, while students are expected to possess proper manners, critical awareness, and caution in interpreting religious texts. The learning materials highlight a gradual understanding of muhkamat and mutashabihat verses, supported by intellectual and ethical discipline. The identified educational methods include exemplary teaching, vigilance against interpretative deviation, consultation, realistic learning, and temporary cessation when misunderstanding arises. The study concludes that the educational values embedded in Sahih Muslim remain highly relevant for strengthening contemporary Islamic education that integrates knowledge, character, and spirituality.